2011
DOI: 10.1055/s-0030-1267102
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bracing versus observation in the treatment of idiopathic scoliosis

Abstract: Study design: Systematic review.Objectives: (1) Does brace treatment compared with observation of curves lead to lower rates of surgery and failure for patients with idiopathic scoliosis? (2) Does brace treatment compared with observation of curves lead to better quality of life outcomes for patients with idiopathic scoliosis? (3) Does brace treatment compared with observation of curves lead to improved curve angle for patients with idiopathic scoliosis?Methods: A systematic review of the English-language lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Eighteen SRs addressed the effectiveness of non-surgical interventions: five SRs addressed SSE methods [33] , [51] [54] , four evaluated manual therapies [6] , [7] , [55] , [56] and five addressed bracing [16] , [24] , [36] , [43] , [57] . Four SRs compared the effectiveness of different interventions: bracing, therapeutic SSEs, lateral electrical surface stimulation (LESS), observation and/or surgery, or else their combinations (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen SRs addressed the effectiveness of non-surgical interventions: five SRs addressed SSE methods [33] , [51] [54] , four evaluated manual therapies [6] , [7] , [55] , [56] and five addressed bracing [16] , [24] , [36] , [43] , [57] . Four SRs compared the effectiveness of different interventions: bracing, therapeutic SSEs, lateral electrical surface stimulation (LESS), observation and/or surgery, or else their combinations (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As the aim of this overview was to analyze existing SRs, potential authors of unpublished SRs were not contacted neither were searches for gray literature, registered titles and review protocols conducted. The exception was one SR [43] for whom the first author was contacted with a request for supporting material mentioned in the paper which was not available from the publisher. An update of a Brace Cochrane review [33] , co-authored by JB-S, being currently under review, was also considered.…”
Section: Methodsmentioning
confidence: 99%
“…Other papers either considered surrogate outcomes (e.g., curve severity, trunk rotation) [ 24 – 26 ] or failed to find relevant studies in terms of study design and/or methodological rigour [ 27 ]. The systematic review, by Davies et al [ 57 ], regarded bracing and other nonsurgical interventions and found limited evidence suggesting that bracing may negatively influence quality of life. Remarkably, Davies et al concluded that it was not known whether bracing was more effective in reducing curve progression than Side-Shift therapy (a method of SSE) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review, by Davies et al [ 57 ], regarded bracing and other nonsurgical interventions and found limited evidence suggesting that bracing may negatively influence quality of life. Remarkably, Davies et al concluded that it was not known whether bracing was more effective in reducing curve progression than Side-Shift therapy (a method of SSE) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…64,66,67 Dolan and Weinstein's 64 evidence-based review critically analyzed the literature to determine a pooled estimate of the prevalence of surgery after observation and after brace treatment in AIS. The review included a total of 18 studies …”
Section: Management Bracingmentioning
confidence: 99%